The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00330-016-4305-7
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of paediatric medical imaging examinations performed at a European teaching hospital over a 7-year period

Abstract: • Medical imaging (MI) examinations are commonly performed in paediatric patients. • In 7 years 95,805 examinations were performed on 39,707 paediatric patients. • Use of ultrasound and MRI in paediatric patients increased annually. • Highest frequency of MI examinations was observed in neonates/infants younger than 1 year. • Awareness of MI utilisation patterns and trends can help inform practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…The absorbed radiation dose resulting from diagnostic and therapeutic NM procedures in pediatric patients is a matter of concern . Portelli et al . recently assessed the frequency of pediatric medical imaging examinations over 7 yr and found that each year, 4 of every 1,000 pediatric patients in the United States likely undergo an NM examination .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorbed radiation dose resulting from diagnostic and therapeutic NM procedures in pediatric patients is a matter of concern . Portelli et al . recently assessed the frequency of pediatric medical imaging examinations over 7 yr and found that each year, 4 of every 1,000 pediatric patients in the United States likely undergo an NM examination .…”
Section: Introductionmentioning
confidence: 99%
“…5-7 Portelli et al 8 recently assessed the frequency of pediatric medical imaging examinations over 7 yr and found that each year, 4 of every 1,000 pediatric patients in the United States likely undergo an NM examination. 8 The frequency of NM examinations is lower than that of other medical imaging modalities in this population; nevertheless, NM procedures should be performed with the lowest possible amount of administered activity necessary to ensure a useful diagnostic result. NM acquisitions are considered to be relatively high-dose diagnostic examinations for children; for example, the estimated effective 18 F-fluorodeoxyglucose dose in such examinations for children aged 1-15 yr ranges from 8.0 to 9.2 mSv, and that for 82 RbCl ranges from 8.3 to 9.9 mSv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 TS-höfuð var algengasta rannsóknin á Landspítala (40,3%) en þó var hlutfall TS-rannsókna af höfði laegra þar en víða annars staðar. 13,15 Mikil notkun TS vegna höfuðáverka barna 20 hefur leitt til þess að gerðar hafa verið klínískar leiðbeiningar 21 meðal annars á íslensku, 22 sem án efa stuðla að viðeigandi notkun. Það er hins vegar viðurkennt vandamál í Evrópu að leiðbeiningar fyrir tilvísandi laekna vantar víða 15 og fáar leiðbeiningar um val myndrannsókna eru til á íslensku.…”
Section: Umraeðaunclassified
“…Magnetic resonance imaging (MRI) of the lung is increasingly established in children and adolescents [1][2][3][4][5][6][7]. According to the recently published systematic review of Hirsch et al [2], lung MRI enables to replace up to 90% of paediatric chest computed tomography (CT) examinations.…”
Section: Introductionmentioning
confidence: 99%